Pessoas em situação de rua de Fortaleza: a expressão da pobreza e modos de enfrentamento - Esmeraldo Filho, Carlos Eduardo (2021)
This research approachs the expression of poverty in the context of homeless people, as well as their ways of coping, based on the following questions: how is poverty manifested among homeless people? What ways of coping practices against poverty are used by people living on the streets? Each question originated two studies, the first of which has the general objective: to analyze the manifestation of poverty among homeless people in Fortaleza-CE; the second aims to understand the ways of confronting poverty implemented by people living on the streets in the city of Fortaleza-CE. This research used quantitative and qualitative approaches. The first enabled the construction of the Multidimensional Poverty Index (MPI) specific for this population, as well as the measurement of multidimensional poverty. A total of 236 homeless people participated, by answering the questionnaire. Using the SPSS 21 software, we performed Analysis of Variance (ANOVA), Analysis of Correlations, Student's t test, Chi-Square test and Descriptive Statistics. The qualitative stage allowed the study of the meanings attributed by the participants about the condition of poverty and coping practices. For data analysis, we used Atlas ti 5.2, based on Bardin's Content Analysis. The multidimensional concept proved to be adequate for investigating the poverty of homeless people, considering the multiplicities of deprivation and the insufficiency of the monetary perspective. Almost all participants are in multidimensional poverty or vulnerable to poverty. Considering the work/income, health, education, subjective and human rights dimensions, the results showed the scope of the precariousness of life on the streets. Just over half of the participants have work activities, usually informally. Those who ask for money are the ones with the greatest multidimensional poverty, while those who receive the Bolsa Família showed less poverty. Despite the support network that helps with food, there are reports of hunger and searching for food in the garbage. On the psychosocial implications of poverty, the results point to self-blame, humiliation and shame. Associated with these processes, the intensity of the rights violations of the homeless population drew attention, with an emphasis on discrimination in the public service and violence of all types. The poorest participants are also the ones who suffer the most violence and discrimination, with the main aggressors being other people living on the streets and the police. The consequences of these practices imply psychosocial suffering and feelings of inferiority. The ways of coping were shown to be associated with the available social support network. The most common practices are of an individual nature, such as begging and work activities, but collective actions were also identified, mainly around the National Movement of the Street Population (MNPR), which, even though incipient, tries to fight for the guarantee of rights and public policy. The conclusions indicate that homeless people experience extreme multidimensional poverty, and it is essential to understand these conditions as a structurally determined process, a result of the current model of neoliberal capitalism.